Cross-species transmission of a feline haemoplasma from domestic to wild cats - Kellner, Annie, author; Antolin, Michael F., advisor; Carver, Scott, committee member; Crooks, Kevin R., committee member; VandeWoude, Sue, committee member (Colorado State University. Libraries, 2016)
Disease poses a substantial threat to rare species worldwide. Spillover of multi-host pathogens from domestic to wild species may occur when a) closely related domestic and wild species co-occur and b) the high-density domestic species acts as a maintenance host with transmission to the rarer wild relative. Wild and domestic felids are susceptible to many of the same pathogens and co-exist near the interface of natural and developed landscapes. Our study evaluates cross-species transmission and host-switching of Mycoplasma haemominutum (Mhm), an erythrocytic bacterial parasite, between free-ranging domestic cats and nine wild felid species. We took a multi-pronged approach to evaluate transmission mechanisms by combining field surveys, modeling, model selection, pathogen genotyping and phylogenetic analyses. Our models consisted of a priori hypotheses of transmission pathways designed to predict observed prevalence data and were parameterized by site- and species-specific information. Using an information-theoretic approach we show that transmission via direct host contact is the most parsimonious hypothesis, which we then validated with genetic analyses. We traced transmission pathways by genotyping part of the bacterial 16S rRNA gene in 60 positive blood samples from domestic cats (n=19), bobcats (n=24), and pumas (n=17) from our extensive sampling efforts in California and Colorado for a total of 73 novel isolates (including co-infected samples). We combined these data with 49 previously described sequences from GenBank, and carried out a partitioned Bayesian phylogenetic analysis reconstructing cross-species transmission events of Mhm on a global scale. The phylogenetic analysis validated our best-fitting models by showing that while Mhm is largely host-specific, cross-species transmission has occurred primarily in one direction following the trophic network from lower to higher levels. Our results are consistent with transmission by direct contact as the major mechanism for pathogen transfer of Mhm, and suggest that wild felids worldwide may be at risk for pathogen spillover from domestic cats.